2005
DOI: 10.1242/dev.01791
|View full text |Cite
|
Sign up to set email alerts
|

Initial formation of zebrafish brain ventricles occurs independently of circulation and requires thenagie okoandsnakehead/atp1a1a.1gene products

Abstract: The mechanisms by which the vertebrate brain develops its characteristic three-dimensional structure are poorly understood. The brain ventricles are a highly conserved system of cavities that form very early during brain morphogenesis and that are required for normal brain function. We have initiated a study of zebrafish brain ventricle development and show here that the neural tube expands into primary forebrain, midbrain and hindbrain ventricles rapidly, over a 4-hour window during mid-somitogenesis. Circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
227
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 190 publications
(244 citation statements)
references
References 61 publications
16
227
1
Order By: Relevance
“…We explored the cellular mechanisms responsible for this anisotropic growth. While the relevance of fluid movement in increasing the size of the cavity has been demonstrated in several experimental models 5,10,11 , with the involvement of paracellular transportation and epithelial chloride secretion 9,23 , its role in shaping the lumen has still not been evaluated. It is widely assumed that the increased intraluminal concentration of chloride (and other ions) promotes the movement of water from outside the organ into the lumen (by paracellular or transcellular transport), similar to what occurs in secretory epithelial organs 12,13 .…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…We explored the cellular mechanisms responsible for this anisotropic growth. While the relevance of fluid movement in increasing the size of the cavity has been demonstrated in several experimental models 5,10,11 , with the involvement of paracellular transportation and epithelial chloride secretion 9,23 , its role in shaping the lumen has still not been evaluated. It is widely assumed that the increased intraluminal concentration of chloride (and other ions) promotes the movement of water from outside the organ into the lumen (by paracellular or transcellular transport), similar to what occurs in secretory epithelial organs 12,13 .…”
Section: Articlementioning
confidence: 99%
“…Lumen growth requires coordination between fluid ingress and increase of the luminal epithelial surface area. Fluids ingress has been shown to rely on a functional Na þ /K þ ATPase pump, the CFTR chloride channel and the formation of both paracellular pores and barriers by claudin proteins 5,[9][10][11] . The present view of the process indicates that fluid ingress is mediated by transepithelial fluid transport, in which the epithelium is considered as a pump driving fluid movement from outside of the organ into the lumen [12][13][14] .…”
mentioning
confidence: 99%
“…Molecular identification of the Na, K-ATPase subunit atp1a1a.1 as the gene affected in m883 for the first time provides genetic evidence for the previously postulated role for an ion pump during establishment of laterality in general. Previously, four other zebrafish alleles of atp1a1a.1 were published (Shu et al, 2003;Amsterdam et al, 2004;Yuan and Joseph, 2004;Lowery and Sive, 2005). While the alleles published by Shu and coworkers (heart and mind, had) and Yuan and coworkers (small heart) appear to be identical, the insertional mutation published by Amsterdam and coworkers has not been described in detail.…”
Section: Discussionmentioning
confidence: 99%
“…A search for candidate genes in this region (www.ZFIN.org) revealed that Chen and colleagues had mapped the mutation heart and mind (had la1 ) to this genomic region and shown that had affects the gene ATPase, Naϩ/Kϩ transporting, alpha 1a.1 polypeptide (atp1a1a.1) (Shu et al, 2003). More recently, other alleles of had have also been published: had hi3475 , a retroviral insertion (Amsterdam et al, 2004), had mw15b (Yuan and Joseph, 2004), and had to273a (Lowery and Sive, 2005), which initially had been described as snk to273a . In collaboration with Dr. Chen (UCLA), we performed complementation analysis of m883 and had la1 , which revealed non-complementation and demonstrated that m883 is an allele of had.…”
Section: The M883 Mutation Causes Left-right Isomerism Of Endodermal mentioning
confidence: 99%
See 1 more Smart Citation